FORMULATION AND IN VIVO EVALUATION OF NANOEMULGEL-CONTAINING COCOA POD HUSK (THEOBROMA CACAO L.) EXTRACT AS TOPICAL ORAL PREPARATION - RAHAYU, YANI CORVIANINDYA; SETIAWATIE, ERNIE MADURATNA; RAHAYU, RETNO PUDJI; KUSUMAWARDANI, BANUN; ULFA, NINIK MAS (International Journal of Applied Pharmaceutics, 2024)
Objective: Cocoa pod husk (Theobroma cacao L.) extract was applied to enhance bioavailability and drug effects due to antibacterial, antioxidant and anti-inflamation agents. Recent years have seen significant development of nanomedicine in non-invasive therapy of oral infection. The aim of this study was to develop the formula of nanoemulgel of Cocoa Pod Husk (CPH) extract for topical oral therapy compared its stability and evaluation in gingivitis rats with gels preparations on different gelling agents. Methods: The topical oral preparation were made in 4 formulations: F1 (CPH gel with gelling agent Sodium Carboxy Methyl Cellulose (Na-CMC) 3%); F2 (CPH gel with gelling agent Carbomer 1%); F3 (CPH nanoemulgel with gelling agent Na-CMC 3%); and F4 (CPH nanoemulgel with gelling agent Carbomer 1%. The physical characterization test of preparations were evaluated the pH, homogeneity, viscosity, spreadability and adhesion test. In vivo evaluation of gingivitis rats were observed using histological analysis of the fibroblast number and gingival collagen density in experimental Wistar rats by Hematoxylin eosin and Masson trichrome staining.Results: Four formulation (F1-F4) showed good stability in pH, viscosity, spreadability and adhesivity (p<0.05). The observation for 7 d after gel application to gingivitis rats, showed that the number of fibroblast and collagen density increasing in the treatment group compared to the control group (p<0.001). In the LSD test, F3 and F4 indicated the highest increase, however no significantly different (p>0.05).Conclusion: Nanoemulgel with Na-CMC as gelling agent potential to be used as an effective carrier for the active ingredients of CPH extract.